2019
DOI: 10.5539/gjhs.v11n11p60
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Term Babies with Persistent Pulmonary Hypertension of the Newborn

Abstract: OBJECTIVE: The study aimed to determine the prevalence of acute kidney injury (AKI) in term neonates with persistent pulmonary hypertension of the newborn (PPHN), to identify the probable risk factors, and to find its relation to mortality. METHODS: The study recruited 758 term neonates admitted to the neonatal ICU (NICU). Diagnosis of PPHN was established on the basis of clinical and echocardiographic criteria. For diagnosis of AKI, we adopted the modified Kidney Disease: Improving Global Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the overall incidence in our study agreed with previous studies. Sheta et al 12 evaluated 47 term infants with PPHN and reported an AKI rate of 34% by using modified KDIGO criteria. Kamolvisit et al 13 found an AKI rate of 28.4% among 109 PPHN infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the overall incidence in our study agreed with previous studies. Sheta et al 12 evaluated 47 term infants with PPHN and reported an AKI rate of 34% by using modified KDIGO criteria. Kamolvisit et al 13 found an AKI rate of 28.4% among 109 PPHN infants.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature on the association between PPHN severity and AKI are limited. Sheta et al 12 suggested a relationship between AKI and severe PPHN diagnosed by oxygenation index. In our study, severe PPHN diagnosed by echocardiography was associated with 5.7 foldincreased risk for AKI.…”
Section: Akimentioning
confidence: 99%
See 1 more Smart Citation